2019
DOI: 10.1007/s00198-019-04914-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical testing of hip protectors following the Canadian Standards Association express document

Abstract: A variety of hip protectors are available, but it is not clear which is the most effective and there is no standard test to evaluate their performance. This is the first study that uses a standard mechanical test on hip protectors. Some protectors perform well but others are almost ineffective, providing little to no protection to the wearer during a fall. Introduction: Each year, over 70,000 patients are admitted to hospital in the UK with hip fractures. There are a variety of commercial hip protectors curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This study has used the same test method for assessing hip protectors (as described in the CSA Standard) to assess the impact properties of a number of commercially available floor samples. These biomechanical testing methods have been previously used to assess the peak force reduction during a simulated fall of eighteen commercially available hip protectors [36]. It is interesting to note that the force attenuation for these hip protectors ranged from 3 -36 %, and in this study the force attenuated by the floor surfaces was 0.7 -25 %.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This study has used the same test method for assessing hip protectors (as described in the CSA Standard) to assess the impact properties of a number of commercially available floor samples. These biomechanical testing methods have been previously used to assess the peak force reduction during a simulated fall of eighteen commercially available hip protectors [36]. It is interesting to note that the force attenuation for these hip protectors ranged from 3 -36 %, and in this study the force attenuated by the floor surfaces was 0.7 -25 %.…”
Section: Discussionmentioning
confidence: 82%
“…The test set-up for the mechanical impact of the flooring has previously been described in an existing study by Keenan et al [36]. A simplified version of the method is given below, but further details can be found in the previous study.…”
Section: Impact Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be broadly classified into hip protectors where padding with soft, energy-absorbing material is used and hip protectors where semi-rigid material is used that diverts the force away from the trochanteric region to the soft tissues of the thigh [ 7 ]. Keenan and Evans performed biomechanical testing using a standardised test to compare individual hip protectors in their effectiveness in preventing hip fractures [ 8 ]. They found that there were significant differences in the effectiveness of individual hip protectors in their ability to reduce the impact forces [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keenan and Evans performed biomechanical testing using a standardised test to compare individual hip protectors in their effectiveness in preventing hip fractures [ 8 ]. They found that there were significant differences in the effectiveness of individual hip protectors in their ability to reduce the impact forces [ 8 ].…”
Section: Discussionmentioning
confidence: 99%